Aquisição da linguagem: uma retrospectiva dos últimos trinta anos - Correa, Letícia Maria Sicuro (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
A survey of the research on language acquisition is presented, in which the major trends, controversies and findings of the last 30 years are highlighted. The study of language acquisition carried out in Brazil is situated within the broader context of the research in this area. The perspectives of a theory of language acquisition are considered.